CONTRIBUTION OF LITERATURE IN SUSTAINABLE DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2022)
This paper is an attempt to explore the contribution of literature in promoting sustainabledevelopment. Various literary works are critically analysed to examine how literature can raise awarenessabout environmental issues, promote social justice, gender equity and inspire individual and collective actiontowards sustainability. Literature can be considered as the mother of all knowledge. It is made of the lifeexperiences. It has the power to shape our perceptions, values, and behaviors. The United Nations haveframed 17 Sustainable Development Goals (SDGs). Literature can play a crucial role in attaining these goals asliterature is closely related to culture. And both literature and culture are connected to sustainability. Byinvestigating the connections between literature, culture, and sustainability, this paper exhibits the potential ofliterature to contribute to a more equitable and environmentally conscious world.